PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) PADA MATA KULIAH TELAAH KURIKULUM FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA SEMESTER III PRODI PENDIDIKAN FISIKA FKIP UNIB - Rosane Medriati; Dedy Hamdani (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This study aims ( 1 ) To enhance the student 's ability to think creatively third semester at college Assessing Physics curriculum using learning model of Creative Problem Solving (CPS) in the Physical Education department of Guidance and Counseling UNIB ( 2 ) To increase the activity of the third semester students on Assessing learning curriculum using learning model Creative Problem Solving ( CPS ) in the Physical Education department of Guidance and Counseling UNIB . This type of research is Classroom Action Research ( CAR). This research was conducted in the Physical Education Program . Subjects were as many as 33 students of the third semester . Student activity data collected by non-test is through observation using the observation sheet , and creative thinking abilities of students were collected through a written test . The data obtained in the descriptive analysis . The results of the study ( 1 ) the application of the learning model of Creative Problem Solving ( CPS ) can enhance the student 's ability to think creative of cycle 1 to cycle 3 with an average of ( 90.90 % -96.9 % ) , especially in the ability of sensitivity , elaboration , fluency , flexibility and originality of the study course curriculum Physical Education III semester students FKIP UNIB ( 2 ) the application of learning models Creative Problem Solving ( CPS ) can increase the activity of the third semester students of cycle 1 - cycle 3 with an average score of ( 24-27 ) especially the activity of expression , thought or idea , opinion or discuss appropriate strategies to solve problems in the subjects of Physics Education Program Curriculum Assessing FKIP UNIB . It is recommended to lecturers to apply this model to other subjects and more creative in developing student learning so that students experience in solving the problem will be more creative and introduction of faculty to students as a whole can help the course of implementation of the CPS models with either.Keywords: learning model Creative Problem Solving (CPS), Assessing Curriculum Physics, ability to think creatively.